A new species of invasive gall wasp (Hymenoptera: Eulophidae: Tetrastichinae) on blue gum (Eucalyptus globulus) in California - la Salle, John; Arakelian, Gevork; Garrison, Rosser W.; Gates, Michael W. (Zootaxa, 2009)
The blue gum gall wasp, Selitrichodes globulus La Salle & Gates, n. sp. (Hymenoptera: Eulophidae: Tetrastichinae), is described as an invasive gall inducer on blue gum, Eucalyptus globulus Labill. (Myrtaceae), in California.